Influenza infection results in local expansion of memory CD8+ T cells with antigen non-specific phenotype and function. (3rd December 2013) - Sckisel, Gail D; Tietze, Julia K; Zamora, Anthony E; Hsiao, Hua-Hui; Priest, Stephen O; Wilkins, Danice E C; Lanier, Louis L; Blazar, Bruce R; Baumgarth, Nicole; Murphy, William J
Summary: Primary viral infections induce activation of CD8 + T cells responsible for effective resistance. We sought to characterize the nature of the CD8 + T cell expansion observed after primary viral infection with influenza. Infection of naive mice with different strains of influenza resulted in the rapid expansion of memory CD8 + T cells exhibiting a unique bystander phenotype with significant up-regulation of natural killer group 2D (NKG2D), but not CD25, on the CD44 high CD8 + T cells, suggesting an antigen non-specific phenotype. We further confirmed the non-specificity of this phenotype on ovalbumin-specific (OT-I) CD8 + T cells, which are not specific to influenza. These non-specific CD8 + T cells also displayed increased lytic capabilities and were observed primarily in the lung. Thus, influenza infection was shown to induce a rapid, antigen non-specific memory T cell expansion which is restricted to the specific site of inflammation. In contrast, CD8 + T cells of a similar phenotype could be observed in other organs following administration of systemic agonistic anti-CD40 and interleukin-2 immunotherapy, demonstrating that bystander expansion in multiple sites is possible depending on whether the nature of activation is either acute or systemic. Finally, intranasal blockade of NKG2D resulted in a significant increase in viral replication early during the course of infection, suggesting that NKG2D is a critical mediator of anti-influenza responses prior to the initiation of adaptive immunity. These results characterize further the local bystander expansion of tissue-resident, memory CD8 + T cells which, due to their early induction, may play an important NKG2D-mediated, antigen non-specific role during the early stages of viral infection.